Modern Brazil: Essays and ideologies - Neto , Antônio Joaquim Pereira; Lima , Rita de Kássia Gomes Novaes de (Seven Editora, 2023)
This chapter presents an expository picture of some of the main essays that carried out the work of interpreting modern Brazil. To expose the ideologies rooted in this genre used by Brazilian intellectuals in the twentieth century, the text points to the different Brazils imagined by scholars such as Gilberto Freyre, Sérgio Buarque de Holanda, Caio Prado Junior, Antonio Candido, Raymundo Faoro, Dante Moreira Leite, Celso Furtado and Carlos Guilherme Mota, who dedicated to the discussion and critical reflection on the formation of the Brazilian people concerned with the construction of their identity in Brazil as a Portugal’s colony, during the empire and as a republic in the process of social and capitalista development. Along the way, cultural, political, and economic ideologies were shaped, which masked some of our fundamental contradictions. DOI:https://doi.org/10.56238/interdiinovationscrese-054